2020
DOI: 10.3390/jcm9061708
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Impact of Breast Cancer Laterality on Clinicopathological, Angiogenic, and Hemostatic Profiles: A Potential Role of Tumor Localization in Future Outcomes

Abstract: To date, lateral differences of invasive breast cancer (IBrC) with respect to the angiogenic and hemostatic profiles were never studied. Here, we aimed to determine the relationship of tumor laterality with various clinical and pathological parameters including angiogenic and hemostatic profiles. A total of 92 women that were initially non-metastatic and treated by surgery were included in this single-center prospective study. Patients were grouped according to tumor localization. A four-year follow-up was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Second, considering the fact that bilateral ovarian cancer develops through synchronous tumorigenesis or metastasis from one side to the other, ovarian cancer involving bilateral ovaries may have more subclinical metastases to the lymph nodes or visceral organs than those involving a unilateral ovary. In colorectal or breast cancer, several investigations have suggested that the survival differences can be attributed to the differences in the molecular and clinical characteristics of right-sided and left-sided tumors [5][6][7][8][9][10]. In the current study, we did not perform such mechanistic investigations.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Second, considering the fact that bilateral ovarian cancer develops through synchronous tumorigenesis or metastasis from one side to the other, ovarian cancer involving bilateral ovaries may have more subclinical metastases to the lymph nodes or visceral organs than those involving a unilateral ovary. In colorectal or breast cancer, several investigations have suggested that the survival differences can be attributed to the differences in the molecular and clinical characteristics of right-sided and left-sided tumors [5][6][7][8][9][10]. In the current study, we did not perform such mechanistic investigations.…”
Section: Discussionmentioning
confidence: 67%
“…In colorectal P A G E cancers, it has been reported that right-sided tumors have poorer survival than left-sided tumors [5][6][7]. Similarly, in breast cancer, several reports have suggested that left-sided breast cancers have poorer survival than right-sided tumors [8][9][10]. In ovarian cancer, two studies reported that patients with left-sided ovarian cancer had a more favorable prognosis than those with right-sided ovarian cancer, presumably because of flow pattern dynamics in the peritoneal cavity or differential flow patterns of the right and left ovarian veins [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from Nigeria, Africa and the western world reported similar patterns (Amer, 2014). Generally, the laterality of invasive breast cancer is proposed to associate with several factors including pro-angiogenic, and pro-thrombotic conditions, and suggested to consider laterality as a prognostic factor of invasive breast cancer (Barbara et al, 2020). The majority of women are right-handed, so it might be easier to detect a palpable lump in the left breast compared with the right (Senie et al, 1980).…”
Section: Discussionmentioning
confidence: 90%
“…Numerous studies have suggested a higher percentage of BC in the left breast than in the right breast [ 63 , 64 , 65 ], including in the cases of bilateral BC [ 66 ]. Furthermore, studies have shown a poor OS of patients with tumors in the left breast and that such tumors were highly angiogenic in nature [ 67 ]. Moreover, certain aspects of BC laterality have been validated in a transgenic EERB2 murine model [ 68 ], showing differences in gene expression in both control and transgenic tumor-bearing mice.…”
Section: Resultsmentioning
confidence: 99%